Intervention of Clinical Pharmacist in the Diabetes Mellitus (Type 2) Management in Outpatients - Mathews , Anju Sarah (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
The objective of this study was to evaluate the impact of clinical pharmacist intervention on glycemic management using fasting blood glucose and glycosylated blood glucose levels. Diabetes Mellitus is one of the world's fastest emerging chronic metabolic diseases which results in significantly raised morbidity, mortality, and healthcare expenses. The International Diabetes Foundation estimates diabetes in one in ten adults and about 47 % are under-diagnosed. Studies have shown that the risk factor for stroke and cardiovascular disease in diabetes patients is 2 to 3 times in contrast to patients having no hyperglycemia. A randomized prospective interventional study was conducted in the outpatient department of a tertiary care hospital. Patients suffering from diabetes for at least 2 years were selected for the study based on the inclusion and exclusion criteria. The control group was not given any special pharmacist care, while the interventional group had a face-to-face interview, counseling, and telephonic follow-up during the study period. Based on the baseline values and endpoint parametric values, the result of the study was analyzed. The study was analyzed based on the difference in the glycemic index, using HbA1c and FBS values. The basal values of HbA1c were similar for both groups (8.5%), but a marked reduction to 7.2% was observed in the interventional group. FBS values reduced from 208 mg/dl to 186 mg/dl in the intervention group, while in the usual care group, the reduction was from 211 mg/dl to 198 mg/dl. HbA1c and fasting blood sugar significantly decreased as a result of the clinical pharmacist's intervention. For the purpose of maximizing pharmacotherapy, the clinical pharmacist participated in patient counseling and education throughout the trial. Through one-on-one meetings, material distribution, and telephone follow-up, it was accomplished. The patient now has a better understanding of how to change their lifestyle in addition to using their medications as prescribed. Through their interactions with the members of the intervention group, the usual care group also felt the effects of the research. Because of this, the standard care group also saw superior clinical results.